Action of multiplicative (generalized)-derivations and related maps on square closed Lie ideals in prime rings - B. Dhara (Математичні Студії)
Let $\mathcal{R}$ be a prime ring and $L$ a nonzero square closed Lie ideal of $\mathcal{R}$. Suppose $F,G,H\colon \mathcal{R}→ \mathcal{R}$\break are three multiplicative (generalized)-derivations associated with the maps $δ,g, h\colon \mathcal{R}→ \mathcal{R}$ respectively which are not necessarily additive or derivations. Assume that $E,T\colon \mathcal{R}→ \mathcal{R}$ be any two maps (not necessarily additive).